1994
DOI: 10.1073/pnas.91.7.2649
|View full text |Cite
|
Sign up to set email alerts
|

Designing amino acids to determine the local conformations of peptides.

Abstract: The local conformations of proteins and peptides are determined by the amino acid sequence. However, the 20 amino acids encoded by the genome allow the peptide backbone to fold Into many conformations, so that even for a smail peptide It becomes very difficult to predict the threedimensional structure. By using empirical conformational energy calculations a set of amino acids has been designed that would be expected to constrain the conformation of a peptide or a protein to one or two local minima. Most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 23 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…w ¼ )34° [50]). According to these values, the Aib u torsion angle deviates less from a-than from 3 10 -helix typical values ()55.2°and )49.9°, respectively [48]) while the w torsion angle is practically the same as the ideal w-value ()34°) for 3 10 helical configurations ()52.2°for a-helix [48]).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…w ¼ )34° [50]). According to these values, the Aib u torsion angle deviates less from a-than from 3 10 -helix typical values ()55.2°and )49.9°, respectively [48]) while the w torsion angle is practically the same as the ideal w-value ()34°) for 3 10 helical configurations ()52.2°for a-helix [48]).…”
Section: Discussionmentioning
confidence: 98%
“…This limitation is imposed by the steric hindrance that arises from its gem‐dimethyl group. The torsion angles for the main‐chain conformation of Aib15 in the family of 40 energy minimized structures are calculated as ϕ = −59.6° ± 1.5 and ψ = −31.9 ± 1.5, while for the mean energy minimized structure they are −56.5° and −31.0°, respectively, close to those of Aib conformational energy minima (ϕ = − 58° and ψ = −34°[50]). According to these values, the Aib ϕ torsion angle deviates less from α‐ than from 3 10 ‐helix typical values (−55.2° and −49.9°, respectively [48]) while the ψ torsion angle is practically the same as the ideal ψ‐value (−34°) for 3 10 helical configurations (−52.2° for α‐ helix [48]).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Aib has been reported to possess a slightly higher intrinsic helical propensity than Ala, which is the most helix-favoring among the 20 protein amino acids ( , ). In this respect, theoretical studies have indicated that the helix-stabilizing effect of Aib is caused by the geminal methyl groups which severely reduce the allowed conformational space and restrict the peptide backbone torsion angles (φ, ψ) to those characteristic of the helical configuration ( 27 , . Therefore, the incorporation of Aib into a polypeptide chain is expected to indirectly stabilize the folded structure by decreasing the chain entropy of the unfolded state.…”
mentioning
confidence: 99%
“…In addition, K59 is a quaternary carbon amino acid replacement analogue. Many studies have shown that the introduction of a quaternary carbon can improve the stability of peptides, making them resistant to proteases. Our results showed that K59 has good stability for four types of bacteria in physiological salt environments and serum.…”
Section: Discussionmentioning
confidence: 99%